Safety and efficacy of repeat long-term incobotulinumtoxinA treatment for lower limb or combined upper/lower limb spasticity in children with cerebral palsy - Kaňovský, Petr; Heinen, Florian; Schroeder, A Sebastian; Chambers, Henry G; Dabrowski, Edward; Geister, Thorin L; Hanschmann, Angelika; Martinez-Torres, Francisco J; Pulte, Irena; Banach, Marta; Gaebler-Spira, Deborah (Journal of pediatric rehabilitation medicine, 2022)
PURPOSE: The open-label phase 3 "Treatment with IncobotulinumtoxinA in Movement Open-Label" (TIMO) study investigated longer-term safety and efficacy of incobotulinumtoxin A in children/adolescents with cerebral palsy (CP). METHODS: Patients on standard treatment, with unilateral or bilateral lower limb (LL) or combined upper limb (UL)/LL spasticity received four incobotulinumtoxinA injection cycles (16 or 20 Units/kg bodyweight total [maximum 400 or 500 Units] per cycle depending on ambulatory status/clinical pattern treated), each followed by 12-16 weeks' observation. Treatment for pes equinus was mandatory; flexed knee or adducted thigh were options for unilateral treatment and/or ULs for unilateral/bilateral treatment. The primary endpoint was safety; changes in Ashworth Scale and Gross Motor Function Measure-66 scores, and Global Impression of Change Scale scores at week 4 of each injection cycle were also evaluated. RESULTS: IncobotulinumtoxinA (≤500 Units for ≤98 weeks) was safe, well-tolerated, and effective across all endpoints for multipattern treatment of LL and combined LL/UL spasticity in ambulant/nonambulant children/adolescents with CP. Treatment effects increased with each injection cycle. No new/unexpected safety concerns were identified. CONCLUSION: IncobotulinumtoxinA showed a good safety and tolerability profile, with efficacy over multiple clinical presentations. As an adjunct treatment, it offers an effective, individualized treatment option for pediatric CP-related spasticity.
Keywords: výsledek terapie; botulotoxiny typu A; svalová spasticita; Type A; Adolescent; movement disorders; paediatric; Child; dítě; dolní končetina; muscle spasticity; Lower Extremity; Neuromuscular Agents; mladiství; Treatment Outcome; Botulinum Toxins, Type A; nervosvalové látky; lidé; Botulinum toxins; Humans; mozková obrna; Cerebral Palsy; Muscle Spasticity; cerebral palsy